The riddle of subjectivity: The Humean notion of the self - Azeri, Siyaves (University of Ottawa (Canada), 2008)
The empiricist-naturalist approach to the self considers the mind's operations to be a function of its openness to the natural world via sense-impressions. Empiricist-naturalist philosophers, who are concerned with the self, more or less, followed the path of the Newtonian natural sciences. It is extremely difficult---as a matter of fact impossible---to locate the empiricist conceptualization of the self within the framework of a rationalist theory of subjectivity, which is based on the subject's undivided sovereignty over both itself and what is non-self. Individualism presupposes the self-sufficiency of the individual subject and its complete self-sovereignty. In this respect, individualism turns to a form of substantialism that detaches the self from the external world. Husserl's egology, for instance, shows that substantialism is inherent even in a pure formalist approach to the question of the self. The efforts of later phenomenologists, such as Max Scheler and Edith Stein, are insufficient in providing a resolution to the question of the self, since these thinkers share and are committed to Husserl's individual-atomistic presuppositions. An empiricist theory of the self would totally be in contrast to such a conceptualization. Hume distinguishes between the self with regard to thought and imagination and the self with regard to passions. This differentiation shows a tension between the substantialist conceptualization of the notion of the self and an empirical-social formulation of this notion. Hume's rejection of the idea of the self signifies the lack of a substantial self and the impossibility of providing any proof for the existence of such a substance. Hume introduces the notion of the self as "a bundle of perceptions." Yet, he is aware that such a formulation concedes the existence of an immanent tension---even a contradiction---within the self: to assume that the self is a perceptual entity is to propose that it is external to itself. We face the problem of explaining how an objective and external entity like the self can acquire an intimate status when one considers one's own being. If we stick to an atomistic-individualistic account of subjectivity we cannot resolve this tension. The very notion of the individual, in such a case, appears as the substantial core upon which the notion of the self is to emerge. Individualism, thus, appears as a form of substantialism. It is reference to the concept of "other," as a societal being, that provides us with the required data to form the idea of the self; such a notion of the self suggests a promising solution to this riddle. The existence of the self is "paradoxical" since such immanent being is rooted in elsewhere than in one's own interior. Psychological studies and philosophical investigations of Vygotsky and members of his school, such as Luria and Leont'ev, show that the existence of the self is paradoxical, merely in the sense that the self pre-requires the other. Such an approach to the riddle of subjectivity can be traced back to Hume's considerations of the notion of the self. Thus, the aforementioned apparently contradictory state of existence of the self would be explained away once we realize the potentials in Hume's interpretation of the problem of the self, which allows characterizing the self as a social being.
Keywords: Philosophy.